Plasmonic properties of metallic nanoparticle layers - Vieira, Bruno Gondim de Melo (2019)
Agglomerates of metallic nanoparticles (NPs) are known for a long time to interact remarkably with light, which leads them to a wide range of applications, from high-resolution imaging to solar cells. The self-assembly technique has drawn attention lately as it allows the synthesis of very close-packed nanoparticle clusters with high parameters precision and relatively low cost. This thesis provides a thorough theoretical investigation of the optical properties of mono-, bi- and few-layers made of gold and silver nanoparticles, showing also crucial experimental results that solidly support the study. Finite-difference time-domain (FDTD) simulations predict the excitation of one bright plasmon mode at the monolayers and two plasmon modes at the bilayers, one bright and one dark mode, identified by the parallel and antiparallel induced dipoles between the layers, respectively. A plane linearly polarized incident wave with propagation normal to the film is used. The dark mode excitation is allowed by field retardation that becomes dominant when the size of the nanoparticles is sufficiently large. The spectral properties of the mode, such as resonance energy and linewidth, can be tuned by changing the nanoparticles sizes and their separation. The simulations predict also a high density of nearfield hotspots with intensity enhancement of up to 3000, which indicates that these materials are excellent for spectroscopy applications. Microabsorbance measurements on gold bi- and trilayers show the characteristic absorbance peak from the dark interlayer modes, confirming the simulation predictions. For other few-layers with higher layer numbers, new dark plasmon modes are excited and a standing wave behavior starts to emerge, in which most of the light gets passed through the material and is no longer absorbed. We investigate the possibility of employing the layers for hot-electron generation, providing both FDTD simulations and time-resolved transient absorption experiments. Furthermore, we observe that placing the layers onto a reflective surface leads to a tremendous increase in the optical absorption of the dark modes. All methods we used are very reproducible and the simulated results can be verified experimentally with a relatively simple setup. This study opens the way for many new explorations in both fundamental and applied research.